Viscosity Approximation Methods with Meir-Keeler Contractions for Nonexpansive Semigroups: Suthep Suantai, Yeol Je Cho, Prasit Cholamjiak - Team, Support (Thai Journal of Mathematics, 2012)
We establish strong convergence theorems of the viscosity approximation method associated with Meir-Keeler contractions for nonexpansive semigroups in a real Hilbert space. The main results improve and extend the corresponding results existed in the literature.